TINJAUAN HUKUM TERHADAP WARGA NEGARA ASING YANG MELAKUKAN PENYALAHGUNAAN VISA IZIN TINGGAL KUNJUNGAN LEWAT BATAS WAKTU (OVERSTAY) - Lukman Supriadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The Indonesian Government, through the Directorate General of Immigration, seeks to support economic growth through the tourism sector to increase foreign exchange resources. The government provides free visa for short visit to foreigners. A visa is a permit (approval) for entry, in the form of a stamp or initials affixed by the officials concerned on the applicant's passport. Foreigners utilize the convenience of free visit visa by committing immigration related violations such as misuse of visa until the residence permit is expired to carry out activities that do not comply with Indonesian immigration law. This article aims to study the implementation of law enforcement by immigration to foreigners who misuse visa overstay visits. The results disclosed how immigration law enforcement acts in accordance with Law Number 6 of 2011 concerning Immigration and Presidential Regulation Number 21 of 2016 concerning Visa Free Visit, by supervising the completion of administrative procedures of visit stay permit for foreigners, and acting administratively to those who violate the permit by charging foreigners to pay the burden of expenses, and deport them to the countries of origin.Keywords: Immigration; Visit Visa; Overstay